Condition monitoring of lithium-ion batteries using broadband multisine excitation and electrochemical impedance spectroscopy - Waligo, Alfred (Department of Electrical Engineering, 2018)
Electrochemical Impedance Spectroscopy (EIS) is a well-known technique that has been employed on various electrochemical cells to obtain their impedance spectra. Lithium-ion(Li-ion) cells are some of the cells to which it has been applied. The impedance spectra obtained from EIS can be used to estimate various batteries State of Health (SOH) and State of Charge (SOC) characteristics. The lengthy acquisition time associated with standard EIS makes it unsuitable for rapid on-line impedance measurements. Alternative methods that take a shorter time have therefore been proposed. This study compares the spectra obtained by the Harmonic Compensated Synchronous Detection (HCSD) broadband signal technique with the EIS and a custom Broadband Impedance Spectroscopy (BIS) technique, at different states of charge, which mimic a real-time load. The test cells are industry standard Nickel-Cobalt and Manganese Oxide (NCM) Li-ion cells. The BIS technique is like HCSD in the selection of frequencies; however, the amplitude of the excitation broadband signal is varied to match the impedance magnitude response of the cell. Also, parameter extraction is performed on both EIS and BIS techniques for fault detection purposes.